Pengaruh Fear Of Missing Out dan Flash Sale Terhadap Pembelian Impulsif Pada Pengguna Shopee : Studi Kasus Pada Mahasiswa Universitas Jambi - A’isyah Amini; Musnaini Musnaini; Hendriyaldi Hendriyaldi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Fear of Missing Out (FoMo) and flash sales on impulsive buying behavior among Shopee users, specifically focusing on students at Universitas Jambi. The rapid development of digital technology and the rise of e-commerce have increased the prevalence of impulsive buying, particularly among younger generations who are highly influenced by social media and online promotions. This research uses a quantitative approach with a survey method involving 100 active students of Universitas Jambi who are Shopee users and have made purchases during flash sale events. The data were analyzed using multiple linear regression to examine the effect of FoMo and flash sales on impulsive buying behavior. The results indicate that both FoMo and flash sales have a positive and significant influence on impulsive buying, both partially and simultaneously. These findings suggest that marketing strategies based on urgency and the fear of missing out are effective in triggering impulsive consumer behavior among students. This research is expected to contribute to the development of more ethical marketing strategies and raise consumer awareness in managing shopping behavior.